Green space and the compact city: planning issues for a 'new normal'. (21st July 2021) - Lennon, Mick
ABSTRACT: The paper traces the emergence of urban public green space as an issue of concern for planning. This is used as a platform to discuss the emergence of the compact city idea and how this conceives the design and use of such spaces. The paper then identifies a series of issues that need to be prioritised in future research for the planning of urban green space in the 'new normal' of social distancing consequent on COVID-19. Issues requiring attention and a series of outline examples of potential solutions are grouped beneath four categories: form & features, distribution, connectivity and resilience.